EFEKTIVITAS ROM PASIF KOMBINASI DENGAN ELEVASI KAKI TERHADAP PERUBAHAN PERFUSI PERIFER PADA PASIEN KRITIS DI RUANG INTENSIVE CARE UNIT (ICU) RUMAH SAKIT BETHESDA YOGYAKARTA TAHUN 2024: CASE REPORT: Effectiveness of Passive ROM Combined with Leg Elevation on Changes in Peripheral Perfusion in Critical Patients in the Intensive Care Unit (ICU) of Bethesda Hospital Yogyakarta in 2024: Case Report - Made Wahyu Ryan Baskara; Diah Pujiastuti; Margaretha Rina Anjarwati (Forind Press, 2024)
Critical patients who experience organ dysfunction can be life-threatening so special monitoring is needed. Critical patients with prolonged bed rest and weakness in the limbs cause poor peripheral vascularization. Non-pharmacological action by carrying out passive ROM combined with leg elevation is useful for improving blood circulation in the periphery. This study aims to identify the effectiveness of passive ROM combined with leg elevation on changes in peripheral perfusion in critical patients in the ICU at Bethesda Hospital Yogyakarta in 2024. The case report method involves carrying out an intervention for 2 days with a duration of 10 minutes. One participant was a critical patient in the ICU Room at Bethesda Hospital, Yogyakarta. The measuring tool uses a supporting data observation sheet and a peripheral perfusion assessment sheet, namely ABI. The results showed an increase in ABI values ​​in patients. The conclusion of this study was that there was an increase in ABI values ​​after passive ROM combined with leg elevation. It is hoped that future research can carry out passive ROM combined with leg elevation to change peripheral perfusion, for example in hemiplegic patients.